Two new species of the chigger mite genus Tateracarus (Acariformes: Trombiculidae). Issue 3 (3rd April 2022) - Stekolnikov, Alexandr A.; Matthee, Sonja
ABSTRACT: The chigger mite genus Tateracarus Goff, 1983 was known from one species, Tateracarus quadrisetosus Goff, 1983, described ex Gerbilliscus leucogaster (Peters) in Namibia. We describe two more species of this genus, Tateracarus kimberleyensis sp. n . and Tateracarus foliosetosus sp. n . collected from Micaelamys namaquensis (Smith) in the Northern Cape Province of South Africa. We also update the diagnosis of Tateracarus . http://www.zoobank.org/urn:lsid:zoobank.org:pub:5F688E91-3A5D-4EF5-A95A-A74EA038FBC7